Software development for prediction of projectiles' flight path - Sunyoto, Eric Tandy (Nanyang Technological University, 2023)
In Singapore, due to the lack of land area, the strategy of high rise buildings has been adopted. Most of the population lives in high-rise buildings such as HDBs and incidents that could occur from living in these buildings are falls from heights. In incidents of fatalities from falls from height, the cause may be uncertain at the time the body is found. Investigations would then be conducted, and evidence gathered to determine the mode of death be it suicide, homicide, or accidental death. In cases where there are no witnesses or cameras around, it can be difficult to ascertain the cause of death. The flight motion of a human body falling from height can be viewed as a projectile motion in kinematics. This project is aimed to help authorities have a simple and convenient way of helping to predict and calculate the cause of death and the height of fall using the laws of physics, a biomechanical approach, and also using the injuries sustained by the victim. A program called Fall Prediction Program is developed using Python and coded with Visual Studio Code. The program will allow users to input information such as the victim’s details, and the building’s information, as well as make use of the autopsy report to input the injury details of the victim.